SECTORAL IMPACT OF GLOBAL FINANCIAL CRISIS AND HIGH FOOD PRICES: A COMPUTABLE GENERAL EQUILIBRIUM (CGE) ANALYSIS FOR SOUTH AFRICAN AGRICULTURE - Fadeyi, Oluwatoba Akinsuyi (Bloemfontein: Central University of Technology, Free State, 2017)
This thesis contains studies that provide theoretical analysis and empirical evidence on the sectoral impact of the global financial crisis and high food prices on the agricultural sectors of South Africa. The study investigates the effects of the global financial crisis on the production, employment, trade and household consumption by using the ORANI-G Model, a static single country computable general equilibrium framework. The results show that a 10% decrease in export as a result of the fall in global demand leads to a decline in GDP and return on capital, and an increase in unemployment at the macro level, while the agricultural sector suffers a decline in production output and household demand.The study also explores the effects of the 2007/08, as well as the 2011 global high food prices on the South Africa economy. The global high food prices was simulated by imposing price shocks of a 25% increase in food prices. When the price shocks are incorporated, the result shows that there is an increase in consumer price and agricultural production, among others. However, there is a sharp decline in household demand for basic items. High and rising food prices undermine food security and threaten the livelihood of the poor. Empirical evidence supports the hypothesis that there are clear links between high food prices and lower caloric intake, lower quality diet, and an increase in malnutrition.
Published Thesis